“Factores asociados y Síndrome de burnout de los cirujanos dentistas del distrito de Trujillo, 2022" - Paredes Pacheco, Wilmer Daniel (2022)
Associated factors and burnout syndrome of dental surgeons in the district of Trujillo, 2022"Objective: To determine the association between sociodemographic factors and Burnout Syndrome of dental surgeons in the district of Trujillo, 2022. Methodology: The type of research is cross-sectional descriptive correlational qualitative variables. Material and Method: The sample consisted of a total of 210 dental surgeons, with a minimum sample size of 199 participants, chosen randomly. A questionnaire was applied in two sections: Sociodemographic Factors and Maslach Burnout Inventory; the sample was made up of 57.1% (120) who were male and 42.9% (90) female. 56.2% (118) were between 22 -34 years old, 31.9% (67) between 35- 47 years old and 11.9% (25) were between 48-60 years old. According to marital status, 57.1% (120) were single and 37.6% (79) were married. Regarding salary, 29.5% (62) received salary between 850 and 1699 soles, 32.9% (69) received between 1700 and 3400, finally those who received more than 3400 soles are 27.1% (57). Those who have consumed medications to control anxiety were 18.1% (38) and those who did not have a medication are 81.9% (172). Regarding the hours of sleep, 61% (128) sleep less than 8 hours a day, 33.8% (71) sleep 8 hours and those who sleep more than 8 hours a day are 5.2% (11) of the total sample. .Results: It was found that 17.6% (37) have no Burnout Syndrome, 71.4% (150) have a tendency to Burnout and 11% (23) have Burnout Syndrome. Taking into account the dimensions of the Burnout syndrome, 58.6% (123) have a medium Emotional Exhaustion, 63.8% (134) have a medium level of Depersonalization and 56.2% (118) have a medium level of personal fulfillment. The sociodemographic factors studied were: age, sex, medication consumption, hours of sleep, marital status and salary. The association of Burnout Syndrome to sex, consumption of anxiety medications and monthly salary was found. Also the association of the Emotional Exhaustion dimension according to sex and consumption of medication for the population's anxiety. Lastly, the association of the personal achievement dimension and monthly salary.Conclusions: The dental surgeons of the District of Trujillo, 2022, present a Tendency to Burnout Syndrome